Electricity pricing regulated, deregulated and smart grid systems - Sen, Sawan; Sengupta, Samarjit; Chakrabarti, Abhijit (CRC Press, Taylor & Francis Group, 2015)
"This book provides proven methods for supplying uninterrupted, quality power at a reasonable price to the consumer. Taking into consideration operating constraints as well as generation cost, line overload, and congestion for expected and inadvertent loading stress, the text presents solutions based on stochastic optimization techniques--such as genetic algorithm, particle swarm optimization, and differential evolution--for improving the stability, reliability, and efficiency of LPS and deregulated multi-bus networks. It also proposes the use of stochastic techniques in optimizing utility management in the smart grid"-- Provided by publisher.